2020
DOI: 10.1007/s11325-020-02207-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of antioxidant vitamins and selenium in patients with obstructive sleep apnea

Abstract: Purpose Obstructive sleep apnea (OSA) is a disorder characterized by recurrent episodes of obstruction of the upper respiratory tract during sleep often accompanied by oxygen desaturations. Antioxidant defense mechanisms are important to prevent OSAassociated diseases and decrease mortality. We aimed to determine the levels of selenium and vitamins A, C, and E in patients with OSA but without any comorbidities and compare the results with a control group, theorizing that the findings may be helpful to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Chen et al [72] demonstrated that selenium concentrations are decreased in newly diagnosed OSA patients with mild to moderate severity. In contrast, Saruhan et al [70] found significantly higher selenium levels in OSA patients compared with healthy subjects. In both studies, patients with comorbidities, which could impact the results, were excluded.…”
Section: The Role Of Antioxidants In Osamentioning
confidence: 84%
See 2 more Smart Citations
“…Chen et al [72] demonstrated that selenium concentrations are decreased in newly diagnosed OSA patients with mild to moderate severity. In contrast, Saruhan et al [70] found significantly higher selenium levels in OSA patients compared with healthy subjects. In both studies, patients with comorbidities, which could impact the results, were excluded.…”
Section: The Role Of Antioxidants In Osamentioning
confidence: 84%
“…Several studies reported decreased levels of vitamins A and E in OSA patients compared with healthy individuals [68,69]. In contrast, Saruhan et al [70] found that concentrations of vitamin A are increased in OSA patients and are positively correlated with AHI. The levels of vitamin E were also higher in OSA patients compared with healthy individuals, but the difference was not statistically significant, possibly due to the different sample sizes of the groups used in the study (47 vs. 114).…”
Section: The Role Of Antioxidants In Osamentioning
confidence: 98%
See 1 more Smart Citation
“…First, There is a report that circulatory selenium concentration is significantly lower in patients with Alzheimer's disease and it is closely related to the level of an antioxidant enzyme, such as glutathione peroxidase [5]. Saruhan et al evaluated the association of serum selenium, vitamins A, C, and E with obstructive sleep apnea (OSA) by considering the antioxidant mechanisms in the pathogenesis of OSA [6]. Serum selenium and vitamin A levels were significantly higher in OSA patients, and there was a doseeresponse relationship between serum selenium concentration and the apnea-hypopnea index.…”
Section: Dear Editormentioning
confidence: 99%
“…It has shown that low Se intake was associated with short sleep (5–6 h) compared with normal sleep (7–8 h) [ 16 ]. Furthermore, a case-control study published in 2020 has found that Se may be an important defense mechanism amongst patients with OSA without any comorbidities [ 17 ]. Rachel et al [ 18 ] also proposed that Se can be used to treat depression, which is the main symptom of sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%